A mycological study of clinically normal nails and waistbands and their role as sources of infection in patients with tinea corporis - Reddy, Asritha; Joseph, Noyal Maria; Khan, Subuh Parvez; Bhat, Shuaeb (International Journal of Research in Dermatology, 2019)
Background: Dermatophytosis is a superficial fungal infection of keratinized tissue caused by keratophilic fungi- dermatophytes. Inanimate objects and infected nails favour the spread of infection. Purpose of this study was to identify the role of waist bands and uninvolved nails as sources of infection in patients with tinea corporis. Methods: A study was carried out on 50 patients with tinea corporis during the period of December 2010 to June 2012 at Tertiary Care Centre at Pondicherry. Nail clippings, waist band cuttings and scrapings were subjected to direct microscopy with 10% KOH and culture. Results: Laboratory analysis showed positive culture in 18% of patients, of which dermatophytes were isolated from all three samples in 12% of patients, while in 6% of the patients growth was seen only in the skin scrapings and waist bands. Conclusions: Waist bands and uninvolved nails harbour dermatophytes and play an active role in the spread and recurrence of infection.